(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
To enhance the European mobility of students, The Bologna Declaration set the introduction of the uniform two-cycle educational system in higher education as an aim, which was extended into a three-cycle system by the Berlin Declaration integrating the doctoral schools. In Hungary the law of 2005. CXXXIX. establis- hed the legal frame to transform the structure and content of the higher education. The new three-level education system was introduced in the health science edu- cation in 2006 with the launch of the basic academic lines. In our study we present the motivating and hindering aspects of this transformation of structure and con- tent that occurred and still occurs at the Faculty of Health Science of PTE. In ad- dition we examine how the educational levels, particularly the basic academic education that has been working for 3 years, can meet the objectives and aims stated in the Declarations.